ACS NSQIP Risk Calculator: An Accurate Predictor of Complications in Major Head and Neck Surgery?. (November 2016) - Prasad, Kumar G.; Nelson, Benton G.; Deig, Christopher R.; Schneider, Alexander L.; Moore, Michael G.
The American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) calculator is meant to provide an estimation of perioperative risk. Our goal was to determine the clinical applicability of the calculator in major head and neck surgery. A retrospective chart review was completed for major head and neck operations performed at 1 institution from 2013 to 2014. The calculated perioperative complication risks from the ACS NSQIP calculator were compared with observed complication rates. Overall, the ACS NSQIP calculator had little predictive value for pneumonia, surgical site infection, 30-day return to operating room, or length of stay within this cohort ( P > .05). The calculator appears to have some value predicting total numbers of complications but has poor performance predicting an individual's risk of suffering a perioperative complication. In conclusion, in our small cohort of patients, the ACS NSQIP calculator was a poor predictor of perioperative complications following major head and neck operations.